Theological Vision of Tribals in Chhotanagpur - Tirkcy, Agapit (Asian Horizons, 2008)
In this article. the author recounts the various tribal myths on creation accessible in the plateau of Chhotanagpur. He illustrates the salient features of the myth on creation as found in the Kurukh. Santal, Munda, Kharia, and 1-10 accounts. Though there are striking similarities in the narratives. there are remarkable dilTerences. On the basis of the accounts, the author points out that there is a clear idea of the Supreme Being as the creator of the world and its creatures. In this article. Agapit Tirkey highlights certain perennial thrusts of tribal theology as eco-Inendly pro-life. life of communion. etc. He concludes his article by drawing the attention of the readers to the closeness of the theological vision of the tribals of Chhotanagpur and the biblical theological vision in the book of Genesis.